2017
DOI: 10.26444/aaem/74200
|View full text |Cite
|
Sign up to set email alerts
|

Health in old age, and patients’ approaches to telemedicine in Poland

Abstract: In Poland in ageing there still dominates the experience of multiple ailments and polytherapy, something which justifies a search for new, easily accessible, and economically sound solutions for health care. Telemedicine is a promising solution although there is a need for concrete steps to be taken to raise willingness amongst geriatric patients to take advantage of telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…Respondents who were neither satisfied nor dissatisfied, were almost twice more at risk of having an ADL limitation. Similar results were obtained by Buliński and Błachnia [47]. A higher socio-economic status, support from one's family, higher satisfaction with one's environment and living in one's own home, all play a key role in good ageing [48].…”
Section: Discussionsupporting
confidence: 81%
“…Respondents who were neither satisfied nor dissatisfied, were almost twice more at risk of having an ADL limitation. Similar results were obtained by Buliński and Błachnia [47]. A higher socio-economic status, support from one's family, higher satisfaction with one's environment and living in one's own home, all play a key role in good ageing [48].…”
Section: Discussionsupporting
confidence: 81%
“…It is reasonable to believe that more frequent use and convenience in technology would correlate with a higher willingness towards telemedicine. In accordance with this consideration, a Polish study examining the willingness to use telemedicine among those 60 years and older showed that 66% of the respondents were reluctant to conduct a video consultation with a physician [ 50 ]. One possible explanation to the counterintuitive age-related results found in our study can be that in times of emergency, the older generation are more likely to trust the authorities in emergency management compared to the younger generation.…”
Section: Discussionmentioning
confidence: 99%
“…This change is visible even in critical areas, such as caring for patients suffering from dementia [15], which is an achievement of the last two decades. However, this progress is much more visible in research papers and publications than in common practice [16,17]. In the everyday life of geriatric patients, diseases are usually treated symptomatically using the cheapest, routine procedures.…”
Section: Discussionmentioning
confidence: 99%